Deriving software design models from a set of business processes - Cruz, Estrela F. (2016)
Requirements elicitation is a crucial activity and one of the first steps in software development process. A popular way to capture and describe requirements is through UML use case models. Transforming require- ment specifications into software design models is a complex and error prone software development activity. Software design usually involves several models, each one representing a different perspective. One of those perspectives is the data perspective which can be modeled using a data model. Although of the importance of this model, few works has been done to derive a data model from use case model. The 4SRS (4-Step Rule Set) method generates a logical architecture of a software-based system, based on a use case model. This paper proposes an approach to adapt and extend the 4SRS method in order to generate a data model supporting the generated logical architecture and the elicited requirements based in a set of business process models.